2002
DOI: 10.1111/j.1365-2621.2002.tb09491.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Residence Time Distribution (RTD) in Food Extruders and Study on the Potential of Neural Networks in RTD Modeling

Abstract: Residence time distribution and mean residence time depend on process variables, namely feed rate, screw speed, feed moisture content, barrel temperature, die temperature and die diameter. Flow in an extruder has been modeled by simulating residence time distribution, assuming the extruder to be a series of continuousstirred-tank or plug-flow reactors. Others have developed relationships for mean residence time as functions of process variables. Better models can be developed using neural networks. As an examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…It has been reported that heat (baking) above 180°C negatively affects the TPC of the grape seed flour [15]. The difference may be attributed to the short residence time usually less than 45 S in extrusion processing [44] as opposed to significantly longer baking times. In support, recently, we found that extrusion technology has a very minimal effect on the loss of water soluble TPC in cherry pomace incorporated in cornstarch, with no significant decrease of TPC in the extruded product [18].…”
Section: Total Polyphenolic Content Of Gp Extrudates Extractsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that heat (baking) above 180°C negatively affects the TPC of the grape seed flour [15]. The difference may be attributed to the short residence time usually less than 45 S in extrusion processing [44] as opposed to significantly longer baking times. In support, recently, we found that extrusion technology has a very minimal effect on the loss of water soluble TPC in cherry pomace incorporated in cornstarch, with no significant decrease of TPC in the extruded product [18].…”
Section: Total Polyphenolic Content Of Gp Extrudates Extractsmentioning
confidence: 90%
“…Previously, the baking process of grape seed flour significantly reduced its antioxidant activity [15]. The difference in time duration of exposure to heat which is less than 45s in extrusion processing [44] can explain the retention of antioxidant activity of the GP extrudates. Based on the physicochemical quality of the extruded products with GP, the addition of 5% GP level in cornstarch processed at 16% moisture level and 150 rpm screw speed is promising to produce healthy extrudates.…”
Section: Effect Of Extrusion On the Total Antioxidant Activities Of Gmentioning
confidence: 99%
“…In reality, the conventional batch processes of manufacturing have several drawbacks (e.g., poor controllability, low yield, and difficult scalability) and are labor intensive [31,32]. Thus, ongoing efforts have focused on the development and optimization of continuous processes.…”
Section: And Hme Processing Technologymentioning
confidence: 99%
“…The limited flexibility, and intensive costs and time taken for drug developments are the major reasons why many industries have moved to using continuous processing approaches. Other important factors governing this move include reducing the size of the manufacturing plant and using available in-house capacity for XXXX [DE1] [30,31]. However, a revision of the manufacturing regulations related to the use of CM will prove it to be beneficial for patients and healthcare systems as a whole [34,35].…”
Section: Applications Via Hmementioning
confidence: 99%
“…The analysis was made based on effects of above process variables on the parameters of the complete model. Ganjyal and Hanna (2002) reviewed the various aspects of RTD in the extrusion process and prospects of using neural network (NN) to model. Ganjyal, Hanna, and Jones (2003) predicted physical properties of waxy cross-linked starches using a NN model.…”
Section: Introductionmentioning
confidence: 99%